2006
DOI: 10.1021/ic051492p
|View full text |Cite
|
Sign up to set email alerts
|

Systematic DFT Study of Gas Phase and Solvated Uranyl and Neptunyl Complexes [AnO2X4]n (An = U, Np; X = F, Cl, OH, n = −2; X = H2O, n = +2)

Abstract: The six-valent uranyl and neptunyl complexes [An(VI)O2X4]n (An = U, Np; X = F, Cl, OH, n = -2; X = H2O, n = +2) have been studied within the framework of density functional theory. The relative stabilities of the cis and trans isomers, structural properties, charge distribution, and ligand binding energies have been determined using the modified Perdew-Burke-Ernzerhof functional at the all-electron scalar relativistic level. Uranyl and neptunyl complexes with different ligands have been compared in a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 95 publications
2
37
0
Order By: Relevance
“…The gas phase DFT studies of Felmy et al 108 The impact of hydroxide on the first solvation shell of uranyl has been documented in both experimental 80,111,112 and computational literature alike. 80,97,98,[113][114][115][116][117][118][119][120][121][122] The EXAFS and XRD analysis by Clark et al 111 While there is broad consensus in the literature regarding solvation structures of the ions in an aqueous environment, the significant range of reported values for both Ca and Sr hydrates suggests that the systematic study presented here will be a valuable addition to the literature as well as provide an accurate basis for the novel investigation of the hydrated ions in the presence of hydroxide. The impact on the solvation environment of alkaline earth metals due to the presence of hydroxide is investigated here for the first time using AIMD methods, with particular attention paid to identification and characterisation of proton transfer events, along with their timescales and frequency.…”
Section: +mentioning
confidence: 81%
“…The gas phase DFT studies of Felmy et al 108 The impact of hydroxide on the first solvation shell of uranyl has been documented in both experimental 80,111,112 and computational literature alike. 80,97,98,[113][114][115][116][117][118][119][120][121][122] The EXAFS and XRD analysis by Clark et al 111 While there is broad consensus in the literature regarding solvation structures of the ions in an aqueous environment, the significant range of reported values for both Ca and Sr hydrates suggests that the systematic study presented here will be a valuable addition to the literature as well as provide an accurate basis for the novel investigation of the hydrated ions in the presence of hydroxide. The impact on the solvation environment of alkaline earth metals due to the presence of hydroxide is investigated here for the first time using AIMD methods, with particular attention paid to identification and characterisation of proton transfer events, along with their timescales and frequency.…”
Section: +mentioning
confidence: 81%
“…At first sight this may seem unlikely, given that experimental data so far have rather indicated that the position of the bands between 20 000-30 000 cm −1 is quite indifferent to the nature of the equatorial field. However, these spectra have always been recorded in an equatorial surrounding that is saturated with ligands ͑be it four chorines, three nitrates, or a combination of ligands in solution spectra͒ 24,25,[41][42][43] A recent CASPT2 investigation of the electronic spectra of uranyl chloride complexes in acetone 40 has confirmed that the excitation energies in such complexes indeed differ by no more than a few hundreds cm −1 between complexes with different numbers of equatorial chlorine/ acetone ligands. The answer to the question whether the complete removal of all ligands from the equatorial plane would indeed introduce a shift in the electronic spectra predicted by the present SAOP-TDDFT or previous CASPT2 calculations can only come from an experimental spectrum of the bare uranyl ion.…”
Section: B Results With Spin-orbit Couplingmentioning
confidence: 99%
“…The advantage of studying actinides using computational techniques is safe and provides more precise understanding before tackling tedious experimental tasks and even can able to guide experimentalists. In recent years, computational approaches have been employed as important tools to predict several essential properties of actinides relevant to nuclear waste management and safe disposal such as electronic structure and bonding 5 , hydration [6][7][8] , speciation [9][10][11][12] , redox chemistry [13][14][15][16][17][18][19][20] , spectral properties [21][22][23][24] , reaction mechanisms [25][26][27][28][29][30][31][32][33] and electron transfer reactions. [34][35][36][37][38][39][40][41] Penta-valent uranyl(V) ions are unstable and readily disproportionate to form U(IV) and uranyl(VI) complexes in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%